A novel approach to determine splitter vane length for an extremely high hub/tip ratio mixed-flow compressor impeller. (June 2020) - Xiang, Hang; Chen, Jiang; Cheng, Jinxin; Song, Xiancheng; Niu, Han
This paper presents an approach to determine splitter vane length in radial compressor impellers based on a modified 1D performance prediction model, which considers the effects of splitter vane length and blade number on impeller internal losses. The splitter vane length corresponding to optimum blade number is investigated to achieve the maximum efficiency of a mixed-flow compressor impeller with an extremely high hub/tip ratio. An empirical formula for calculating splitter vane length is proposed. CFD results show that blade number and splitter vane length have a complex coupling interaction which makes it inappropriate to be described by equivalent solidity or effective blade number. 1D results and CFD verification indicate that optimum full-length blade number is 42 and corresponding splitter vane length is 20% of full-length blade length at design flow rate. The impeller peak efficiency mainly depends on minimum loss superposition of blade loading, skin friction and tip clearance. With the increase of splitter vane length and blade number, blade loading loss and clearance loss decline while skin friction loss increases.